Methodical approaches to classification and estimation of elements of investment activity: selected theoretical aspects - Pankou, Mikalai M. (Journal of the Belarusian State University. Economics, 2019)
The article examines the issues of regulation of investment activity in the Republic of Belarus as a complex economic system through the separation of its constituent elements. The division of clusters into constituent elements of investment activity contributes to the division of interests of individual subjects of investment activity. In conclusion, the author comes to the conclusion that the investment potential of the Republic of Belarus is the progressive development and use of the investment component of the economic system of the regions and regions of the state in order to achieve a socioeconomic effect in terms of achieving effective results for all participants in the investment process.